Zonotope-based Interval Estimation for Discrete-Time Linear Switched Systems. Issue 2 (2020) - Zhang, Wenhan; Wang, Zhenhua; Raïssi, Tarek; Dinh, Thach Ngoc; Dimirovski, Georgi M.
Abstract: This paper is concerned with the interval estimation for discrete-time linear switched systems affected by unknown disturbances and noises. A novel interval estimation approach is proposed by integrating robust observer design with zonotopic techniques. By introducing L ∞ technique into observer design, the proposed approach is effective in attenuating the influence of unknown disturbances and noises, and improving the accuracy of interval estimation. Based on the designed observer, the interval estimation can be obtained by using zonotopic analysis. Numerical simulation results are conducted to demonstrate the feasibility and effectiveness of the proposed approach.